Myositis non-inflammatory mechanisms: An up-dated review. Issue 2 (4th March 2017) - Manole, Emilia; Bastian, Alexandra E.; Butoianu, Niculina; Goebel, Hans H.
ABSTRACT: Idiopathic inflammatory myopathies (IIM) represent a heterogeneous group of rare muscular diseases, with no clearly known causes. IIM frequently have an incomplete response to treatment due to the difficulty in distinguishing between IIM forms, and due to neglect their non-inflammatory causes. Important data concerning non-immune mechanisms in IIM pathology have been recently accumulated. There is a correlation between inflammatory and non-inflammatory mechanisms, but their involvement in IIM pathogenesis is still unknown. Here we review some of the most important data regarding the non-immune IIM pathology, highlighting possible future therapeutic targets: endoplasmic reticulum stress, ATP metabolism, ROS generation, autophagy, and microRNAs disturbances.